FABP4 and I-FABP Levels in Pregnant Women Are Associated with Body Mass Index but Not Gestational Diabetes - Tamara Vorobjova; Aili Tagoma; Ija Talja; Helis Janson; Anne Kirss; Raivo Uibo (Journal of Diabetes Research)
Objectives. Gestational diabetes mellitus (GDM) is glucose intolerance detected initially during pregnancy. GDM poses an increased risk for the development of diabetes later in life. Fatty acid-binding protein 4 (FABP4) is a regulator of lipid metabolism and is associated with obesity, insulin resistance, and type 2 diabetes. Increased level of intestinal fatty acid-binding protein (I-FABP) may indicate impaired intestinal permeability, which may be an important contributor to the pathogenesis of type 1 diabetes and GDM. We aimed to compare FABP4 and I-FABP levels in pregnant women with GDM and in healthy pregnant controls, taking into consideration their prepregnancy body mass index (BMI), past exposures to enteroviruses (EV), and adipokine and cytokine levels, which have been shown to decrease insulin sensitivity. Material and Methods. Forty patients with GDM (median age 30.5) and 40 pregnant healthy controls (median age 31.1) were divided on the basis of their prepregnancy BMI into two groups: normal weight (BMI<25, n=20) and overweight (BMI≥25, n=20). FABP4 and I-FABP were measured from serum samples using commercial ELISA kits. Results. FABP4 and I-FABP levels did not differ between women with GDM and healthy pregnant controls (p>0.05 for both comparisons). However, both levels were associated with BMI (p<0.001 for both comparisons). Median I-FABP level was the highest in healthy controls with lower BMI (<25) (p=0.0009). FABP4 levels correlated with BMI and C-peptide values in both groups (p<0.001). Anti-EV antibody levels did not correlate with FABP4 or I-FABP levels. FABP4 and adiponectin levels were negatively correlated in controls (r=−0.61, p=0.0009), while I-FABP correlated positively with adiponectin (r=0.58, p=0.04) and resistin (r=0.67, p=0.04) levels in the GDM group. Conclusion. FABP4 and I-FABP levels were not dependent on the diagnosis of GDM, but rather on BMI. The correlation of I-FABP with adiponectin and resistin levels in women with GDM may suggests the importance of lipid metabolism in GDM-associated changes in intestinal permeability.